Chapter Higher Education in Post-Covid19: The Digital Transformation of Work-Integrated Learning Programmes - FRISON, DANIELA (Studies on Adult Learning and Education, 2023)
Due to the Sars-Cov-2 health emergency and the forced stoppage of regular teaching and traineeship activities, digital work-integrated learning models have been widely proposed to Higher Education students. Blended practices and experiences referred to as virtual or simulated work-integrated learning or digital workplace learning are emerging as instrumental in achieving several educational outcomes and, among them, a positive attitude toward Professional Learning and Development. The contribution intends to reflect on the main issues that the Higher Education systems have been facing during the pandemic, with a specific focus on the management of internship and work-integrated learning activities and projects, and the possible widening of the definition of work-integrated learning.